Insights from density functional theory calculations into the effects of the adsorption and dissociation of water on the surface properties of zinc diphosphide (ZnP2) nanocrystals. Issue 46 (22nd November 2021) - Farkaš, Barbara; Živković, Aleksandar; Uahengo, Veikko; Dzade, Nelson Y.; de Leeuw, Nora H.
Abstract : The effects of hydration/hydroxylation on the surface structure, composition, stabilities, morphology, and electronic properties of β-ZnP2, an emerging absorber materials for photovoltaic applications is unravelled. Abstract : Zinc phosphides (ZnP2 and Zn3 P2 ) are emerging absorber materials for photovoltaic applications owing to their abundancy and non-toxic nature. Herein, we provide a comprehensive characterisation of the surface structure, composition, stabilities, morphology, and electronic properties of both bare and hydrated/hydroxylated low-Miller index surfaces of β-ZnP2 by means of density functional theory (DFT) calculations. Mechanistic insights into the fundamental aspects of water adsorption and dissociation, including the adsorption geometries, energetics, and structural parameters along the reaction path are systematically characterised. The stabilities of the surfaces under dry and wet conditions are discussed in detail and the predicted phase diagrams for the water adsorption are presented. Using calculated surface energies, we have derived the equilibrium morphology of the β-ZnP2 nanocrystals under vacuum and upon hydration or hydroxylation. Atomic-level insights into the origin of the incipient oxidation of β-ZnP2 surfaces are provided through analysis of Bader charges, which reveal that the Zn sites to which H2 O and OH species are bound undergo oxidation due to the transfer of charge to the adsorbed species. Adsorption-induced changes to the electronic properties before and after hydration/hydroxylation were characterised by the work function and partial density of states. The results highlight the need for protection of β-ZnP2 nanocrystals against possible oxidation in the presence of water through post-synthesis organic functionalisation.